Construction of a CRISPR/Cas9-mediated genome editing system in manipulating OsART1 from Oryza sativa cv. Inpago 5 - MIFTAHUL HUDA FENDIYANTO; EKO SETIAWAN; MENTARI PUTRI PRATAMI; IFAN RIZKY KURNIYANTO; FANDRI SOFIANA FASTANTI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Fendiyanto MH, Setiawan E, Pratami MP, Kurniyanto IR, Fastanti FS. 2025. Construction of a CRISPR/Cas9-mediated genome editing system in manipulating OsART1 from Oryza sativa cv. Inpago 5. Biodiversitas 26: 920-927. Understanding the mechanism of aluminum (Al) tolerance in rice (Oryza sativa) cv. Inpago 5 can be done by mutating the ART1 gene to see which Al tolerance genes have decreased expression globally. This study aimed to construct a pRGEB32 vector containing sgRNA-ART1 derived from rice cv. Inpago 5. The construction of the pRGEB32-sgART1 vector was carried out by designing sgRNA, restriction-ligation, transformation, plasmid isolation, verification of target inserts, and sequencing of sgRNA-ART1. The results indicate that the construction of the recombinant vector pRGEB32-sgRNAART1 was carried out by combining digestion and ligase reactions. The construction of the recombinant pRGEB32 construction showed a high level of success in this study. The success of the ART1 sgRNA amplicon in recombinant Escherichia coli indicated this. Annotation studies showed that the pRGEB32 cassette plasmid sequence showed more than 99% homology with the recombinant pRGEB32-sgART1 sequence, especially only 1% was different, namely 20 bp of sgRNA that appeared different. After checking with alignment on the plasmid annotation using the MAAFT alignment method, it was found that 20 bp of ART1 sgRNA was successfully inserted into the pRGEB32-sgART1 recombinant vector. In conclusion, the construction of pRGEB32-sgART1 in this study was successful and showed the presence of a 425 bp band amplicon for the insertion from the region between M13 reverse and sgRNA-ART1.